THE DEVELOPMENT OF CAI BASED ANDROID IN SOLAR SYSTEM AND UNIVERSE TOPIC FOR TENTH-GRADE - M Marwiyah; R Rusijono; Fajar Arianto (Department of Geography Education, University of Jember, 2019)
The aim of the research to generate learning media, thus the media development will assist students to understand the content during the learning process. Besides establishing a product, the manual guide was also arranged. The method used was Research and Development (R & D) model, the validation result of content expert I and II obtain a very good category and media experts I and II also obtain a very good category. The result of individual test is categorized very well with percentage of 91.01%, the result of small group test is categorized very well with percentage of 91.43 %, the result of the large group test is categorized very well with percentage of 89.60%. Hence, based on the result of Android-based CAI media development of Geography in solar system and universe topic of tenth-grade in Al-Iftitahiyah High School needs to be developed and utilized as a learning media that could support the teaching and learning process. Keywords: Development, CAI Based on Android, Geography References Arikunto, Suharsimi. (2006). Research From the whole result h Procedure A Practice Approach. Jakarta: PT. RienekaCipta. Dwinata, R. A. Rusdi, E. Sal, P. Y. (2016). Rancang Abngun Aplikasi Tabel Periodik Unsur Dana Perumusan Senyawa Kimia Dari Unsur Kimia Dasar Berbasis Android. Jurnal Rekursif, 4(2). Retrieved fromhttps://ejournal.unib.ac.id/index.php/rekursif/article/view/888/1207 Januszewski, A. & Molenda, M. (2008). Educational Technology. New York: Lawrence Erlbaum Associates. Kurniawan, Dian. (2015).Android-based Computer Assisted Instruction (Cai) Media Development About Immune Systems in Xi Class Biology in Public High School 1 TarikSidoarjo: http://jurnalmahasiswa.unesa.ac.id/index.php/jmtp/article/view/13450. Market share held by mobile operating systems in Indonesia from January 2012 to July 2017. (2017).https://www.statista.com/statistics/262205/market-share-held-bymobile-operating-systems-in-indonesia/. Rusijono & Mustaji. (2008). Learning Technology Research. Surabaya: Unesa University Press. Sadiman et al, (2007). Media Pendidikan. Jakarta: Raja GrafindoPersada. Setiyadi, Didik. (2016). Media Pembelajaran Untuk Anak Sekolah Dasar Tentang Pengenalan Tata Surya Menggunakan Metode Computer Assisted Intruction (CIA). Information Management For Educators And Professionals, 1(1). Retrieved fromhttp://www.ejournal-binainsani.ac.id/index.php/IMBI/article/view/155/274 Subagyo, Edwardo. (2015). Pengembangan Media CAI Berbasis Android Pada Mata Pembelajaran Bahasa Daerah Materi Aksara Jawa Untuk SiswaKelas X Di SMKN 2 Buduran. Jurnal Mahasiswa Teknologi Pendidikan, 6(3). Retrieved from https://jurnalmahasiswa.unesa.ac.id/index.php/jmtp/article/view/13723/12578 Sudjana,Nana&Rivai, Drs.Ahmad. (2010). Teaching Technology. Bandung: Sinar Baru Algensindo. Sudjana. (2001). Participatory Learning Methods & Techniques. Bandung:Falah Production. Sugiyono. (2009). Educational Research Methods. Bandung: Alfabeta. Sugiyono. (2010). Qualitative Quantitative Research Methods and R & D. Bandung: CV Alfabeta. Sugiyono. (2015). Qualitative Quantitative Research Methodsand R&D. Bandung: Alfabeta. Susilana, Rudi &Riyana, Cepi. (2007). Instructional Media. Bandung: CV. Wacana Prima. Suwignyo, Jati. (2016). Penerapan Model Pembelajaran Computer Assisted Intruction Untuk Meningkatkan Kompetensi Teknik Membuat Aplikasi Laba Rugi SMK Kristen Salatiga. Skripsi. Retrieved fromhttps://lib.unnes.ac.id/23357/1/5302411089.pdf Tinambunan, Arnita. Guidio, L. Melda, P. (2018). Perancangan Aplikasi Rambu-rambu Lalu Lintas Untuk Anak Usia Dini Bebasis Android Menggunakan CAI (Computer Assisted Intruction). Jurnal Riset, 5(3). Retrieved from https://ejurnal.stmik-budidarma.ac.id/index.php/jurikom/article/view/843/728 Tresnanto, Edo. (2017). Pengembangan Media Cai Super-t Bebasis Aplikasi Android Materi Satuan Ukur Mata Pelajaran Matematika Kelas IV SD. Jurnal Penelitoan Pendidikan Guru Sekolah Dasar (JPGSD).Retrieved from https://www.neliti.com/id/publications/254389/pengembangan-media-cai-super-t-berbasis-aplikasi-android-materi-satuan-ukur-mata Copyright (c) 2019 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License